Resistência à educação a distância na educação corporativa - Brauer, Marcus (2008)
Although the technologies resistance is indeed an usual problem within the companies, researches in this area are fragmental, non-cumulative and rare in literature. Nowadays, the resistance to Distance Education [DE] is a significant problem, although this type of learning technology has a high level of growing in many countries. The aim of this research was to identify and analyze the main dimensions of resistance to the DE in Corporative Education [CE]. After bibliography revision of themes like Distance CE, Technologies Resistance, and Unified Theory of Acceptance and Use of Technologies [UTAUT], a theoretical structure was developed and tested which aimed to explain the Resistance to DE in CE. The initial hypotheses of this research has defended that such resistance is caused by eight factors: Self-efficacy, IT Competence, Performance Expectations, Effort Expectation, Social Influence, Facilitating Conditions, Interactivity and Internal Communication. From the Structural Equation Modeling Technique, the initial hypotheses were tested and the results have shown that, in the researched sample, the dimensions Self-efficacy and Performance Expectations has a direct and positive influence regarding DE Resistance in CE, and Effort Expectation, Facilitating Conditions and Interactivity dimensions are constructs previous to Performance Expectations. Such results can be an allowance in management decisions regarding implementation and maintenance of distance courses. By theoretical point of view a DE Resistance scale was created and validated, and also a theoretical DE resistance structure in CE elaborated – The READEC Structure. Finally, future researches suggestions are presented here.